2000
DOI: 10.1007/10719724_7
|View full text |Cite
|
Sign up to set email alerts
|

An Asymmetric Public Detection Watermarking Technique

Abstract: Abstract. The new watermarking technique 1 presented in this paper is an example of an asymmetric public detection scheme. The detection process does not need the original picture nor the secret key used in the embedding process. It is the translation, in the watermarking domain, of a public key pair cryptosystem. The key idea is to filter the pseudo-noise sequence before embedding it in the cover-content. Contrary to classical techniques, the heart of the detection algorithm is not a correlation measure but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 14 publications
0
26
0
2
Order By: Relevance
“…Although the proposed solution was not at all secure, it stressed the issue that the would-be secret key of DSSS can not remain a secret in some applications. Recently, new asymmetric watermarking schemes have been proposed as an interesting alternative especially for the copy protection framework [24], [25], [26], [27], [28], [29]. Although invented independently, the authors showed that these methods shared the same detection algorithm (i.e.…”
Section: Asymmetric Watermarking Methodsmentioning
confidence: 99%
“…Although the proposed solution was not at all secure, it stressed the issue that the would-be secret key of DSSS can not remain a secret in some applications. Recently, new asymmetric watermarking schemes have been proposed as an interesting alternative especially for the copy protection framework [24], [25], [26], [27], [28], [29]. Although invented independently, the authors showed that these methods shared the same detection algorithm (i.e.…”
Section: Asymmetric Watermarking Methodsmentioning
confidence: 99%
“…In such schemes, knowledge of the public detection key must not enable an adversary to remove the embedded watermark. There have been some proposals for asymmetric watermarking schemes based on different approaches such as properties of Legendre sequences [62], "one-way signal processing" techniques [37], or Eigenvectors of linear transformations [31]. Unfortunately, none of these schemes is sufficiently robust against malicious parties [30].…”
Section: Motivationmentioning
confidence: 99%
“…There are several ways to deal with the first two security concerns without using a TTP. One way is to employ asymmetric watermarking schemes such as [22,15,13], in which the key to embed a watermark into a work is different from the key required during detection. Unfortunately, known methods are not satisfactory and there are a number of successful attacks [12].…”
Section: Related Workmentioning
confidence: 99%